EXPLORING THE APPLICATION OF THE ESSENTIAL ELEMENTS OF DANCECREATIVITY IN DANCE EDUCATION - Ya-Fen, Chen (E-Journal VFU, 2024)
he purpose of this research is to try to implement the concept of choreography in the dance curriculum, which uses the introduction and guidance of the basic elements of choreography and adds the concepts of trajectory, level and relationship to inspire students to think about choreography, which can be integrated into the dance curriculum as a 217 stimulus for thinking about choreography